Shanghai Street Style. - Johnson-Woods, Toni (Intellect Books - Street Style Ser., 2013)
Although fashion fixtures and A-list celebrities pack the front rows at the biggest, most glamorous shows at fashion week, the most creative attire is often found not on the catwalks or inside the auditoriums but on the streets.